Pengaruh Pemberian Ekstrak Bawang Merah dan Kecambah dengan Pemberian Pupuk Cair Hayati terhadap Pertumbuhan Seedling Manggis (Garcinia mangostana L.) - ., Rugayah; Karyanto, Agus; ., Ermawati; Suselawati, Dewi (Universitas Lampung, 2021)
Mangosteen (Garcinia mangostana L) seeds from seed, or commonly called seedling, have relatively few lateral roots and are poor in root hairs so that their growth is slow (having a long juvenile period of up to 10-15 years). For this reason, it is necessary to make efforts so that mangosteen seedlings can have a good root system through the addition of natural growth regulators. The purpose of this study was to determine the effect of red onion extract, a mixture of onion extract and mung bean sprouts combined with biological liquid fertilizer on the growth of mangosteen seedling. This research was carried out in the Horticulture FP greenhouse in March 2020–July 2020. This study was arranged in a factorial (3 x 2) in a Randomized Block Design (RAK) with three replications. The first factor was natural ZPT treatment: without extract, red onion extract 400 g/L, and mixed extract of onion 200 g/L and green bean sprouts 200 g/L. The second factor is the provision of biological fertilizers, namely without biological fertilizers and 15 ml/L). The results showed that the administration of mixed extracts of shallots and mung bean sprouts tended to have better growth which could be seen from the highest average value for the variable plant height 6.04 cm, stem diameter 2.93 mm, and the number of secondary roots. The mixed extract treatment of shallots and mung bean sprouts also increased the widest leaf area by a difference of 3.5 cm² compared to the control. Keywords : extract of shallot/ green bean sprout, growth regulator, mangosteen